Indoor multiband antenna for wireless mobile broadband communication - Fadoul, Moubachir Madani (2013)
The development of wireless communication systems and services has caused great demands in designing multiband for mobile communication. Therefore LTE (Long Term Evolution) is a new high-performance air interface standard for mobile communication systems. It is the last step toward the 4th generation (4G) of radio technologies designed to increase the capacity and speed of mobile telephone networks. LTE provides ultra-broadband speeds for complex multimedia applications by using a high performance antenna Since it allows users to access network services wirelessly. In high performance of LTE antenna’s applications where size, weight, cost, performance, ease of installation are constraints, low profile antenna is very much required. To meet these requirements Indoor Multiband Antenna for wireless Mobile Broadband is preferred. This project describes the design of A Monopole Planar antenna operates in five bands: GSM (890–960 MHz), DCS (1710–1880 MHz) and LTE2.7 MHz .applications. By using transmission line feed A Monopole Planar antenna was designed, simulated and, fabricated and measured. The measurements are conducted in anechoic chamber in Wireless Communication Centre, WCC. With the aid of using CST (Computer Simulation Technology-2010), AutoCAD,FR4 board, UV Equipment, Sigma Plot 10 software and Marconi Scalar Analyzer 6204. The antenna satisfied the LTE applications. Analysis showed that the antennas provide better return loss.